2011
DOI: 10.1093/ecam/nep237
|View full text |Cite
|
Sign up to set email alerts
|

Cassia auriculata: Aspects of Safety Pharmacology and Drug Interaction

Abstract: Safety pharmacology studies help in identifying preclinical adverse drug reactions. We carried out routine safety pharmacology with focus on cardiovascular variables and pharmacokinetic herb-drug interaction studies on rats fed with standardized traditional hydro-alcoholic extract and technology-based supercritical extract of Cassia auriculata for 12 weeks. Our studies indicate that both these extracts are pharmacologically safe and did not show any significant adverse reactions at the tested doses. The tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“… 58 Several phenolic compounds, namely (-) catechin, (-) epicatechin and procyanidin B 1 were identified in aqueous alcoholic extract of cassia seeds. 59 Puranik et al. 59 reported on cardiovascular safety and good tolerance of Cassia seed extracts without any adverse effects in male and female rats.…”
Section: Antioxidant Activities and Bioactivities Of Herbal Beveragesmentioning
confidence: 99%
See 2 more Smart Citations
“… 58 Several phenolic compounds, namely (-) catechin, (-) epicatechin and procyanidin B 1 were identified in aqueous alcoholic extract of cassia seeds. 59 Puranik et al. 59 reported on cardiovascular safety and good tolerance of Cassia seed extracts without any adverse effects in male and female rats.…”
Section: Antioxidant Activities and Bioactivities Of Herbal Beveragesmentioning
confidence: 99%
“… 59 Puranik et al. 59 reported on cardiovascular safety and good tolerance of Cassia seed extracts without any adverse effects in male and female rats. However, Cassia seed extracts obtained using supercritical fluid extraction interfered with the absorption of metformin when co-administered with extracts in a rat model.…”
Section: Antioxidant Activities and Bioactivities Of Herbal Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after coadministration, edible plants may reduce the permeability of the conventional drug in the intestinal tract, and may also affect its metabolism in the liver and cause hypoglycemia. Research by Puranik and colleagues found that the technology-based supercritical extract of Cassia auriculata caused a significant reduction in absorption of metformin indicating the need to include pharmacokinetic herb-drug interaction studies to avoid unexpected side effects (Puranik et al, 2011). Another case is the commonly used herb St. John's wort.…”
Section: Safety and Toxicity Of Edible Plants From Tcmmentioning
confidence: 99%
“…[3] Studies have concluded the safety profile of CA for anti-hyperglycemic and hypoglycemia activities. [45] The mechanism through which the CA could act is due to its insulinogenic action. In addition, altered glucose homeostasis improved by feeding the extract through amelioration in the carbohydrate metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%